Effects of Perceived Scarcity on Financial Decision Making - Cook, Laurel Aynne and Sadeghein, Raika (Journal of Public Policy & Marketing, 2018)
How are financial decisions compromised as scarcity increases? Extant research focuses mostly on the consequences of financial scarcity; moreover, this factor is treated simply as a lack of liquidity. Using a mixed-method approach, the authors investigate the dimensions of perceived scarcity and the ways they work in tandem to negatively influence perceptions and decisions. Internal influences (including perceived consequences) and external influences (including decreased lending options) lead to results described in this article as the “triple scarcity effect.” Experimental results show how perceived financial scarcity undermines loan decisions, particularly for consumers at the greatest financial risk. Next, qualitative data collected from the Consumer Financial Protection Bureau are used for a between-method triangulation of the earlier findings. Understanding the multidimensionality of perceived financial scarcity is important for designing preventive measures that improve decisions (e.g., not reborrowing) and decision making (e.g., accurately calculating cost). Results from two interventions demonstrate how these improvements are made when consumers' perceptions of scarcity are reduced. Finally, the authors discuss the welfare impact for lenders, marketers, and policy makers, and they offer an agenda for future research.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTUwOS9qcHBtLjE2LjE1Nw